Bacterial biofilm and its role in antibiotic resistance - Shabana Sharif; Ashok Kumar Yadav (The Microbe)
A biofilm is a dense aggregation of microbial cells encased in an auto-generated matrix of proteins, DNA, and polysaccharides. Bacterial biofilms result in chronic illnesses due to their increased resistance to antibiotics, disinfectants, and the body's immune system. Patients' morbidity and mortality are raised by biofilms because they give bacteria a barrier of defense and resistance to antibiotics. An oxygen and nutrient gradient from the top to the bottom layer of biofilms is another important feature of biofilms. The quiescent cells that cause some of the antibiotic resistances are associated with the gradients and they have doubled rates and lower metabolic activity. With early treatment or aggressive antibiotic prophylaxis, as well as ongoing suppressive therapy, infections caused due to biofilms can be prevented or cured. This review covers bacterial biofilm formation, composition of biofilm, development of antibiotic resistance and tolerance in bacteria due to biofilm formation, and the generation of persistent cells that produce antibiotic resistance in bacteria.